Neutrophil-to-lymphocyte ratio on admission is an independent risk factor for the severity and mortality in patients with coronavirus disease 2019. Issue 2 (February 2021) - Wang, Shijie; Fu, Lingli; Huang, Kejie; Han, Jianglong; Zhang, Rui; Fu, Zhenming
Highlight: The level of NLR on admission could be an independent risk factor for the severe disease and the mortality of COVID-19. The predictive value of NLR for poor prognosis was more significant in patients without other potential risk factors. NLR could help physicians rapidly identify high-risk patients and adopt timely intervention.